Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 3: Derivatives - Section 3.2 - The Derivative as a Function - Exercises 3.2 - Page 115: 19



Work Step by Step

Use derivative formula; $f(x)= x^n \implies f'(x)= n x^{n-1}$ Consider $s(t) = 1-3t^{2}$ Thus, $s'(t) = 0 - 3(2)t^{2-1}= -6t$ and $s'(-1) = -6(-1)=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.